2018
DOI: 10.1155/2018/1463940
|View full text |Cite
|
Sign up to set email alerts
|

Growth Differentiation Factor-15 as a Predictor of Idiopathic Membranous Nephropathy Progression: A Retrospective Study

Abstract: Idiopathic membranous nephropathy (IMN) is a major cause of nephrotic syndrome. No biomarker to predict the long-term prognosis of IMN is currently available. Growth differentiation factor-15 (GDF-15) is a member of the transforming growth factor-β superfamily and has been associated with chronic inflammatory disease. It has the potential to be a useful prognostic marker in patients with renal diseases, such as diabetic nephropathy and IgA nephropathy. This study examined whether GDF-15 is associated with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Moreover, in DN patients, high levels of GDF15 are associated with a decline in estimated glomerular filtration rate and faster progression to kidney failure [ 57 ]. Surely, the enhanced levels of GDF15 can deliver information about the deterioration of kidney function [ 60 , 61 , 62 ]. However, the suitability of GDF15 as a precise marker for kidney disease needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in DN patients, high levels of GDF15 are associated with a decline in estimated glomerular filtration rate and faster progression to kidney failure [ 57 ]. Surely, the enhanced levels of GDF15 can deliver information about the deterioration of kidney function [ 60 , 61 , 62 ]. However, the suitability of GDF15 as a precise marker for kidney disease needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…GDF-15 has also been associated with fibrosis in diseases of other organ systems such as dilated cardiomyopathy [28], systemic sclerosis [29], and chronic liver disease [30]. Two recent studies have shown GDF-15 to be associated with biopsy-proven fibrosis in the kidneys, the first in patients with IgA nephropathy [31] and the other in idiopathic membranous nephropathy [32]. GDF-15 might therefore also be a marker or a causative factor of kidney fibrosis that is responsible for decreased renal function in our pediatric cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Na et al [11] demonstrated that plasma GDF-15 has an inverse correlation with eGFR and is associated with poor renal outcomes in patients with IgA nephropathy, and Ham et al [10] reported similar trends in patients with idiopathic membranous nephropathy. Higher levels of GDF-15 predicted faster decline of renal function in patients with type 1 DM who have nephropathy [8] and starting dialysis in light chain amyloidosis patients [23].…”
Section: Discussionmentioning
confidence: 99%